(untitled) (Fiep Bulletin - online, 2014)
In the last decades, obesity has got the attention of many specialists and become a field for the development of several researches and intervention programs. The difficulty losing and maintaining the corporal weight for a long period of time, the ingestion of greasy food, and a sedentary physical behavior contribute to increase corporal weight, which leads to obesity. Specialists are concerned with adolescence due to difficulty in changing habits established in previous ages. In order to control obesity in adolescence as well as in other ages, some developed countries have created strategies such as educational programs, media campaigns focusing schools, communities, parks, etc. In this work we intend to explain and provide pertinent information about the etiology of obesity, its classification, present occurrence, causes, treatment and prevention world programs. We hope this work will help to promote programs of prevention and treatment of obesity in different age groups, but mainly in childhood and adolescence.